Pedagogies for leading practice - Cheeseman, Sandra; Walker, Rosie (Routledge, 2019)
"Bringing together the experiences of professionals from around the world, this essential text explores the intersections between pedagogy and leadership to consider how effective Pedagogical Leadership can be used to foster the collaborative engagement of children and their families, staff and practitioners, and ensure high quality provision in early years settings and services. Pedagogies for Leading Practice showcases a vast range of experiences and ideas which are at the heart of professional practice. Written to provoke group discussion and extend thinking, opportunities for international comparison, points for reflection, and editorial provocations will help students, policy-makers and others engage critically with wide-ranging approaches to leadership in early years practice. Considering varied forms of collaborative working, the challenges involved in becoming a pedagogical leader, and the role of management in meeting insitutional demands and the needs of the wider community, chapters are divided into four key sections which reflect major influences on practice and pedagogy: - Being alongside children - Those who educate - Embedding families and communities - Working with systems Offering insight, examples and challenges, this text will enhance understanding, support self-directed learning, and provoke and transform thinking at both graduate and postgraduate levels, particularly in the field of early childhood education and care"--